2011
DOI: 10.1007/s11224-011-9736-9
|View full text |Cite
|
Sign up to set email alerts
|

Accurate theoretical IR and Raman spectrum of Al2O2 and Al2O3 molecules

Abstract: The accurate harmonic vibration frequencies together with the infrared (IR) and Raman intensities of the most stable conformers of Al 2 O 2 and Al 2 O 3 molecules have been calculated by the density functional theory (DFT) method with B3LYP exchange-correlation potential and using a set of the augmented correlated consistent basis sets up to quintuple order. The anharmonic vibration frequencies of the non-linear Al 2 O 2 molecule have also been calculated. The obtained equilibrium geometrical parameters, harmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…This is in line with the most recent findings, which showed that the inclusion of electron correlation favors the square over the linear. 42,46,54 At ∼3 eV above Square-Al 2 O 2 (X 1 A g ), we locate the non planar Rhombic-Al 2 O 2 (X 1 A 1 ). The newly characterized C 2v structure and the weakly bound AlOOAl and OAlAlO isomers lie higher in energy (at ∼5 eV).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This is in line with the most recent findings, which showed that the inclusion of electron correlation favors the square over the linear. 42,46,54 At ∼3 eV above Square-Al 2 O 2 (X 1 A g ), we locate the non planar Rhombic-Al 2 O 2 (X 1 A 1 ). The newly characterized C 2v structure and the weakly bound AlOOAl and OAlAlO isomers lie higher in energy (at ∼5 eV).…”
Section: Resultsmentioning
confidence: 73%
“…The vibrational signature of larger aluminum oxide clusters has been obtained by Infrared Resonance Enhanced Multiphoton Ionization spectroscopy (IR-REMPI) by van Heijnsbergen et al, illustrating the effect of the size of the cluster on the spectra. In addition, theoretical calculations, which provided structural and some spectroscopic data, have been performed on different aluminum oxide molecules and small clusters: AlO, , Al 2 O, AlO 2 , Al 2 O 2 , ,, Al 2 O 3 , Al 3 O, Al 4 O, Al n O ( n ≤ 10), Al n O 2 , Al 2 O n ( n = 1–4), and Al x O y ( x = 1–4, y = 1–4). , …”
Section: Introductionmentioning
confidence: 99%
“…The intensity of these peaks is tripled for the sample annealed at 1200 °C, whereas the ones found in the craters are less pronounced. The latter can be assigned to the various Al x O y species formed due to the high‐temperature oxidation of AlN. The two bands at 1370 and 1400 cm −1 , which are found for the sample annealed at the highest temperature, indicate AlC 2 and Al 2 H 6 species, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Mitin [115] used DFT to show that the most stable conformers of gas-phase Al 2 O 2 and of Al 2 O 3 have similar energy and stability. Small differences between calculated and earlier reported experimentally determined harmonic frequencies have been observed which can be eventually reduced by calculating anharmonic vibrational frequencies for all types of molecular geometries.…”
Section: Issuementioning
confidence: 99%